Predictors of community pharmacists’ readiness to implement deprescribing of inappropriate medications for older adults in Qatar - Marwa Elshazly; Sondus Jawad; Ayesha Ahmed; Hager ElGeed; Kazeem Babatunde Yusuff (PLoS ONE, 2026)
There is a paucity of studies focused on the predictors of community pharmacists’ readiness to deprescribe inappropriate medications for older adults especially in developing settings. The study aimed to use the situational theory of leadership to determine community pharmacists’ readiness to implement deprescribing of inappropriate medications for older adults, and as well as its significant predictors. A theory-driven cross-sectional assessment of the readiness (knowledge and confidence) of 252 community pharmacists was conducted in Qatar with a pre-tested 40-item questionnaire. Knowledge and confidence were assessed with a 2-point and 4-point Likert-type scale respectively. The maximum obtainable score for readiness was 16. Readiness was categorized as high (≥ median) or low (<median). Bivariate logistic regression was used to identify the significant predictors. The response rate was 79.4% (200). The majority of the community pharmacists were females (54.5%), within the age range of 20–40 years (88.0%), had BSc / BPharm as the highest educational qualification (70.5%), were full-time employee (97.0%) and consisted mainly of 5 nationalities (91.0%). The median (IQR) readiness score for community pharmacists was 13 (4) (minimum = 4, maximum = 16). Overall, 54.4% (109) of community pharmacists reported high confidence score (≥ median), while 60.5% (121) reported high knowledge score (≥ median). Readiness score was significantly higher among female community pharmacists (p = 0.048) and respondents who reported exposure to deprescribing in undergraduate training (p = 0.001). Overall, community pharmacists felt knowledgeable and confident to implement deprescribing of inappropriate medicines for older adults. However, a number of critical readiness gaps requiring educational interventions especially regarding how to access and use deprescribing toolkits and algorithms were identified. The most significant predictors of community pharmacists’ readiness were gender (female) and exposure to deprescribing in undergraduate training.